PRE-SERVICE EFL TEACHERS’ PERCEPTIONS AND ACTUAL PRACTICES OF GIVING ORAL FEEDBACK IN APPRENTICESHIP PROGRAM: EXPLORATORY STUDY - wati, atikah; Prawiro, Indra Yoga (Wiralodra English Journal, 2019)
The purposes of this study were to know the pre-service EFL teachers? perceptions of their own oral feedback in apprenticeship program and to investigate the types of oral feedback that pre-service EFL teachers use in apprenticeship. It is supported by some problems found in the previous year apprenticeship program,  pre-service teachers were seldom to give feedback to their students? work or performance during the teaching and learning process, those pre-service teachers seem to be afraid to give more information or explanation about students? work, tell the students? incorrect work and give the students the correct answer explicitly, correct the students pronunciation, restate the correct form of students? utterances, etc. To achieve the purpose of study, the writer used qualitative research method. The research participants were be taken from English Department students of Wiralodra University Indramayu that applied for apprenticeship program, there were 20 students that experienced their apprentceship program in several schools in Indramayu. The instrument of the research were observation and questionnaire modified from Sultana (2015). The finding showed that pre-service teachers? were aware by the important of oral feedback to correct students? mistakes, clarify the incorrect information, correct the students? pronunciation, and restate the correct form of students? utterances. Unfortunately in the teaching and learning process many of pre-service teachers did not execute oral feedback when they have to. Most of the oral feedback given to the students were focused on mispronunciation, grammar and vocabulary. Pre-service teachers seems did not notice misinformation mistakes and did not really aware of giving advice on students? performance as the improvement strategy